2016
DOI: 10.4329/wjr.v8.i10.829
|View full text |Cite
|
Sign up to set email alerts
|

Role of molecular imaging in the management of patients affected by inflammatory bowel disease: State-of-the-art

Abstract: AIMTo present the current state-of-the art of molecular imaging in the management of patients affected by inflammatory bowel disease (IBD).METHODSA systematic review of the literature was performed in order to find important original articles on the role of molecular imaging in the management of patients affected by IBD. The search was updated until February 2016 and limited to articles in English.RESULTSFifty-five original articles were included in this review, highlighting the role of single photon emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…A number of novel imaging technologies are emerging that complement or may even replace endoscopy as the gold standard for clinical diagnosis, as recently reviewed in detail [ 10 , 11 ]. Chromoendography involves the application of dyes onto the mucosa, improving endoscopic characterization of lesions and neoplasia, and has the potential to correlate with histological damage, although the latter remains controversial [ 12 ].…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…A number of novel imaging technologies are emerging that complement or may even replace endoscopy as the gold standard for clinical diagnosis, as recently reviewed in detail [ 10 , 11 ]. Chromoendography involves the application of dyes onto the mucosa, improving endoscopic characterization of lesions and neoplasia, and has the potential to correlate with histological damage, although the latter remains controversial [ 12 ].…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Gadolinium-contrasted MRI has recently been shown to reliably predict severe fibrosis in CD and, interestingly, also revealed that areas of fibrosis often coexist with inflammation within the same intestinal segment [ 20 ]. A recent comprehensive review of the use of PET/SPECT for IBD diagnosis, prognosis, and follow-up indicated that 2-deoxy-2-[ 18 F]fluoro- d -glucose ( 18 F-FDG) coupled with CT has the highest accuracy for detecting inflammation in IBD [ 11 ]. 18 F-FDG is a radiolabeled glucose analogue that detects tissue glucose metabolism and has been the tracer of choice for PET studies for decades; however, radiolabeled leukocytes are also typically used to assess GI inflammation.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Clinical studies support the use of PET, SPECT, and MRI for detecting inflammation in the gastrointestinal tract, satisfying the criteria for reduced invasiveness and real-time information (4,5). However, current clinical PET, SPECT, and MRI approaches in IBD are restricted to using radiolabeled autologous leukocytes and 18 F-FDG in PET and SPECT and using gadolinium contrast in MRI, none of which provides information on specific mediators.…”
mentioning
confidence: 99%
“…However, prospective multicenter studies on larger patient samples are needed for validation. 72 Wang et al 73 reported that ultrasonography with clinically translatable dual-targeted (P-and E-selectin) contrast microbubbles specifically enables detection and quantification of inflammation in a murine acute colitis model, leveraging the natural pathway of leukocyte recruitment in inflammatory tissue. They also demonstrated that ultrasonography imaging with contrast shows a correlation well with fluorodeoxyglucose uptake on PET/CT imaging.…”
Section: Evaluation Of Disease Activity and Prediction Of Therapeuticmentioning
confidence: 99%